ANALISIS PERBEDAAN KINERJA KEUANGAN KEMENTERIAN KELAUTAN DAN PERIKANAN REPUBLIK INDONESIA ANTARA OPINI WAJAR TANPA PENGECUALIAN DENGAN OPINI DISCLAIMER - Indriyani; Luthfiana Tarida (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2018)
UU No. 17 of 2003 states that financial statements must be audited by the BadanPemeriksa Keuangan (BPK). Based on Reports on Audit Results of the Central GovernmentFinance Report of the Kementerian Kelautan dan Perikanan (KKP) in 2015 got a WTPopinion and decreased in 2016 the KKP obtained a disclaimer opinion because goodsshopping was 209 billion vessels, of which 756 new units were realized 48 units. Based on thedifferences in opinion, the purpose of the study is to analyze the differences in financialperformance of the KKP between those who get WTP opinions and opinions of disclaimers.This type of research is a causal-comparative study with a sample of data from theKKP's financial performance report on WTP opinions and disclaimer opinions. Data analysiswas performed by Mann Whitney test using SPSS software.The results of the descriptive statistics calculation show that the financial performanceof the KKP which got the WTP opinion with a performance score of 6.0678 was higher thanthe one who got the disclaimer opinion with a performance score of 4.37307. However, thesignificance of the financial performance of the Ministry of Maritime Affairs and Fisheries(KKP) on WTP opinions is no different and no better than those who have a disclaimeropinion. This is concluded based on the Mann Whitney test results where the Asymp value.Sig. (2-tailed) = 0.631≥0.05.